Innovation in tradition: the shifting function of Acehnese wedding stage from marriage reception to customary ritual as a mechanism of cultural inheritance - Lindawati Lindawati; Syakir Syakir; Ponimin Ponimin; Eko Sugiarto (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
The Acehnese wedding stage has undergone changes in terms of shape and decoration, which is also accompanied by a shift in its function. This research aims to explore the shifting functions of the Acehnese wedding stage, which is typically used during wedding receptions but is now also employed in several traditional events, serving as an educational medium. The method used in this research is a descriptive-analytical approach with a qualitative orientation. Research data were collected through in-depth interviews with auction business owners and traditional leaders, observation of Acehnese wedding ceremonies, and documentary studies. Data were analyzed through the stages of reduction, data presentation, verification, and conclusion drawing. The research findings identified that there are three main functions of Acehnese wedding stages: first, as a reinforcement of cultural identity in rituals such as circumcision and seven months of pregnancy; second, as a socio-political representation that symbolizes local pride in welcoming guests of honor and other public contexts; and third, as an educational instrument in museums and tourism settings for cultural preservation and transmission. The findings highlight Aceh's cultural resilience by positioning the wedding stage not only as a passive visual culture but as an active medium that adapts to contemporary realities. These findings form the basis of recommendations for policymakers in designing cultural preservation strategies that are adaptive and contribute significantly to the survival of traditional cultural heritage for future generations.